THE POSITION AND LEGAL STATUS OF CHILDREN OUT OF MARRIAGE ARE REVIEWED BASED ON LEGAL PROVISIONS IN INDONESIA - Abdul Rokhim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The civil rights of children outside of marriage have an impact on the child, because they do not receive legal protection, such as the care and welfare of the child, including the child's right to inherit. The position of an illegitimate child will be a burden for the mother and the mother's family, and the child's legal status is also not covered by the law, such as determining the child's legitimacy, such as the status of the child's birth certificate. Therefore, the author wrote this to identify the legal status of illegitimate children. This writing is prescriptive normative legal research, to answer legal issues raised with arguments, theories or new concepts as prescriptions in solving the problems faced. "Children born out of wedlock only have a civil relationship with their mother and her mother's family." Article 280 KHUPer "With the recognition of a child out of wedlock, a civil relationship is created between the child and his father or mother." Article 100 KHI "Children born out of wedlock only have a family relationship with their mother and their mother's family." Article 49 paragraph (2) Law number 24 of 2013, amendment to Law Number 23 of 2006 concerning Population Administration "Recognition of children only applies to children whose parents have entered into a valid marriage according to religious law, but not yet legal according to State law." Based on the writing, the recognition of an illegitimate child (biological product) as a recognized child means that it will give rise to alimony rights, birthright rights and inheritance rights for the child from his biological father. An illegitimate child only has a lineage relationship, maintenance rights and obligations as well as inheritance rights and relationships with his mother and his mother's family, not with his natural (genetic) father/father or natural (genetic) father/fatherKeyword: children outside of marriage, legal status of children, civil rights of children, legal protection of children